Best Interest of the Child (á¸¤ifáº“ al-AwlÄd) Principle in Adjudicating Marriage Dispensation for Under-Age Couples - Moch. Nurcholis; Iffatin Nur; Abd. Holik; Ahmad Muhtadi Anshor (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
Since the enactment of Law Number 16 of 2019, which amended Law Number 1 of 1974 on Marriage, the Religious Court of Malang Regency has experienced a significant surge in marriage dispensation applications compared to the period when the previous Marriage Law was still in effect. This research aims to construct the concept of maqÄá¹£id asy-syarÄ«â€™ah fÄ« á¸¥ifáº“ al-awlÄd by analyzing judicial reasoning of judges in determining marriage dispensations at Malang Regency Religious Court. It specifically explores how judgesâ€™ interpretations of the best interests of the child can be formulated into a new derivative of maqÄá¹£id theory. This research is a normative-empirical juridical research with a case approach. The data were collected through interviews with three male judges and two female judges from the Religious Court of Malang Regency. Informants were selected using purposive sampling, targeting judges with the most extensive experience in handling marriage dispensation cases. As data saturation had been reached, the number of informants was deemed qualitatively representative. Data were also obtained from official documentation of legally binding marriage dispensation rulings (inkracht van gewijsde). All data were analyzed using a descriptive-analytical approach, and conclusions were drawn through the application of an interactive cyclical method. The principle of the best interests of the child in determining marriage dispensations aims at providing protection for the child, both physically and psychologically. It includes the age of the prospective bride and groom, economic adequacy, reliable guidance and assistance from the family, and adequate religious safety and protection of children in the womb.